Pembuatan Aplikasi E-Service Library untuk Pengelolaan Perpustakaan di SMA N 4 Kota Solok - Negara, Boby Das Prawira; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
This Papper disscusses the making E-Service Library application for library management in SMA N 4 Solok city. This study describe how the application of E-Service Library service library management in SMA N 4 Solok city. Data collected through observation and ditect interview to the SMA N 4 Solok city library.Web based applications for library management are expected become a tools for digital library services in order not to missed the application of technology in the field academic in Senior High School. Application design of E-Service Library for library management SMA N 4 Solok City used three Software supporting applications such as Xampp version 3.2.2, Google chrome or mozilla firefox and Dreamweaver. So, the making E-Service Library application for library management in school made to make things easier librarian facilitate in carrying out its main work that serves the user.Keyword: application, E-Service, management library.